Estudo de comparação institucional para solução de controvérsias para eleições de chefes regionais na Indonésia e no Brasil (Research, Society and Development, 2020)
This article is a legal research which conducts a comparative study of the dispute resolution institutions between the Indonesian and Brazilian elections. The purpose of writing this article is to map the similarities and differences in the practice of dispute resolution between regional head elections in Indonesia and Brazil to take good aspects that are suitable for implementation in Indonesia. In the discussion, it also covers the practice of organizing elections, election management organs and institutions, including the practice of dispute resolution for Election / Pilkada in both countries. The research method used is normative legal research using primary legal materials in the form of statutory regulations and court decisions, using a comparative approach, a statutory approach and a conceptual approach. Conclusions from the discussion of the research results, the authors propose two institutional options for Pilkada dispute resolution in Indonesia: a) Establishing a special election / election court under the PTUN environment. This Special Judiciary is domiciled in each provincial capital to adjudicate and decide on election result disputes (Election / Pilkada Crime and also examine and adjudicate election / election / election process / administration disputes), or b) Define the authority of the Constitutional Court of Justice to adjudicate disputes over the results of the Pilkada (in addition to PHPU) without any differentiation of regime.